Revealing lexical bundles of non-native English essay at a private Islamic university: A corpus-based evaluation - Fauzul Etfita; Sri Wahyuni; Arimuliani Ahmad; Wasana Saranga Sudusinghe; Chandima Kumara Walpita Gamage (Universitas Muhammadiyah Malang, 2025)
Lexical bundles are a crucial element for Foreign Language Learners (FLL) as they facilitate the acquisition of new vocabulary and enhance fluency. Such multi-word statements confer a natural structure to language and enhance successful communication in both spoken and written forms. Although numerous studies address lexical bundles, research on their application in English writing or inside Indonesian EFL classes is notably scarce. The study employed a corpus methodology, utilizing AntConc software version 3.5.9 to categorize lexical bundles from student essays. The output comprised 17,100 varieties of N-gram lexical bundles, specifically three, four, five, and six-word bundles. The study revealed regular use of formulaic and repetitious bundles, including